2016
DOI: 10.12809/hkmj164869
|View full text |Cite
|
Sign up to set email alerts
|

Associations between diabetic retinopathy and systemic risk factors

Abstract: Introduction: Diabetes mellitus is a systemic disease with complications that include sight-threatening diabetic retinopathy. It is essential to understand the risk factors of diabetic retinopathy before effective prevention can be implemented. The aim of this review was to examine the association between diabetic retinopathy and systemic risk factors.Methods: A PubMed literature search was performed up to May 2016 to identify articles reporting associations between diabetic retinopathy and systemic risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 40 publications
9
89
3
4
Order By: Relevance
“…As demonstrated in previous studies, however, multiple factors (e.g. older age, longer duration of diabetes, complicated with other chronic diseases) play a role in the development and progression of diabetic retinopathy [10,17,20], hence it is necessary to remind people with diabetes that good blood glucose control alone may not entirely prevent the development of diabetic retinopathy [21].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in previous studies, however, multiple factors (e.g. older age, longer duration of diabetes, complicated with other chronic diseases) play a role in the development and progression of diabetic retinopathy [10,17,20], hence it is necessary to remind people with diabetes that good blood glucose control alone may not entirely prevent the development of diabetic retinopathy [21].…”
Section: Discussionmentioning
confidence: 99%
“…DR currently affects almost 100 million people worldwide and is becoming an ever-increasing health burden, with estimates between 1990 and 2010 showing that DR-related visual impairment and blindness increased by 64% and 27%, respectively [2]. Several risk factors have been associated with DR, while good glycemic and blood pressure control are considered the most important modifiable risk factors to reduce the risk of progression of DR and vision loss [3]. However, recent studies have shown that the improvement in visual acuity and DR severity score after intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents seem to be independent of baseline HbA1c [4].…”
Section: Commentarymentioning
confidence: 99%
“…During the pathogenesis of T2DM, many risk factors and genetic variants are involved, such as drinking, hyperlipidemia, etc. [3]. Among these factors, the associations between alcohol drinking and T2DM have been widely studied [4,5].…”
Section: Introductionmentioning
confidence: 99%